Concentrate on forward-thinking farmers who are not shy of technology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Lack of food security is a recurring nightmare for many African countries ? their governments and their people...